ANALYSIS OF FACTORS INFLUENCING THE EXISTENCE OF CULINARY VENDORS ON THE BEACH AREA AFTER 13 YEARS OF TSUNAMI (STUDY CASE : LAMPUUK BEACH, ACEH) - Maulida, Zenitha; Indah, Dewi Rosa (Universitas Pamulang, 2018)
After 13 years of tsunami, Aceh has become one of tour destinations which offered various tours, especially Lampuuk beach tour. Recently, it has risen up from adversity. All tours area, especially Lampuuk beach tour progresses rapidly after tsunami. One of the tour developments was marked by growing and developing small-medium enterprises around the area which was currently more focused on culinary sector. In 2011, theMinistry of Tourism and Creative Economy included culinary as a subsector of creative economy. On the average, the culinary vendors built gazeboes to the visitors so that they could enjoy the scenery. The culinary provided by the traders was not luxurious, so it might be accepted by all society levels, starting from snacks to grilled fish as a typical menu of Aceh seashore. The goal of the study was to find out the factors supporting theexistence of culinary vendors around Lampuuk Aceh beach tour after 13 years of tsunami which hit Aceh. The result showed that there were two dominant factors influencing the them. The first factor was the internal factors that consisted of the raw materials availability, the venture capital, simple material processing, labors, and turnover received factors, while the second one was the external factors, such as competitor’s existence and vendors’retribution factors.